1990
DOI: 10.1111/j.1476-5381.1990.tb12054.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epithelium removal on relaxation of airway smooth muscle induced by vasoactive intestinal peptide and electrical field stimulation

Abstract: 1 We have studied the effect of epithelium removal on relaxation of guinea-pig isolated tracheal smooth muscle induced by vasoactive intestinal peptide (VIP) or stimulation of non-adrenergic, non-cholinergic (NANC) inhibitory nerves. Also examined were the effects of inhibitors of neutral endopeptidase (NEP) and angiotensin-converting enzyme (ACE).2 Epithelium removal produced a 3.6 + 0.4 fold leftward shift in the VIP concentration-response curve. The supersensitivity to VIP, following epithelium removal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Similar inter-and intra-species heterogeneity has also been observed for other relaxant agonists such as adenosinc [26,27] and methylxanthines such as theophyllinc [28.29]. In some animal species epithelium removal also enhances tracheal smooth muscle sensitivity to relaxation induced by vasoactive intestinal peptide (VIP) [30].…”
Section: Relaxant Agonistsmentioning
confidence: 71%
“…Similar inter-and intra-species heterogeneity has also been observed for other relaxant agonists such as adenosinc [26,27] and methylxanthines such as theophyllinc [28.29]. In some animal species epithelium removal also enhances tracheal smooth muscle sensitivity to relaxation induced by vasoactive intestinal peptide (VIP) [30].…”
Section: Relaxant Agonistsmentioning
confidence: 71%
“…This is likely to be due to the enhanced stability of RO5024118 to neutral endopeptidase release from the epithelium of these isolated tissues. Other studies have shown that decreasing the neutral endopeptidase activity in isolated airway tissues by treating with inhibitors or removing the epithelium leads to enhanced VIP‐induced relaxation (Farmer and Togo, 1990; Tam et al ., 1990; Groneberg et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…VIP is also inactivated by epithelial neutral endopeptidase (NEP) [5] or by mast cell chymase and tryptase [32]. Recently, it was demonstrated that VIPinduced airway relaxation is enhanced by peptidase inhibitors in the epitheliumdenuded airway [10].…”
Section: Discussionmentioning
confidence: 99%